It is High Time that Journals Underscore the Indispensable Nature of Statistics in Scientific Research - Viswa Chaitanya Chandu (Wolters Kluwer Medknow Publications, 2021)
The role of biostatisticians in scientific research is poorly defined. Majority of manuscripts submitted to scientific journals do not receive statistical advice at as many stages as it requires and neither do they get subjected to a thorough statistical review as an integral part of the peer-review mechanism. This raises concerns about the validity of research findings, especially in light of the increasing reports on the incidence of statistical misuse in health-care research. It is high time that journals emphasize on statistical review of research submissions to ensure scientific validity.